Hermeneutics in Contemporary Interpretation: A Critical Study of the Methods of Qur'anic Interpretation in the Modern Era - Rum, Muhammad (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This research examines the application of modern hermeneutical approaches to Qur'anic interpretation in the contemporary era, analyzing the integration of Western interpretive theories with classical Islamic exegetical traditions. Using qualitative library research methodology with textual, comparative, and conceptual approaches, the study investigates how contemporary Muslim scholars navigate between traditional tafsir methodologies and modern hermeneutical frameworks. Classical exegetical methods developed by scholars like al-Tabari, al-Zamakhshari, and al-Razi remain authoritative but were formulated in specific historical contexts. Contemporary challenges including gender equality, religious pluralism, bioethics, democratic governance, and human rights require new interpretive tools. Pioneering scholars such as Fazlur Rahman, Nasr Hamid Abu Zayd, Mohammed Arkoun, and Amina Wadud have applied hermeneutical concepts emphasizing the distinction between eternal principles and historically conditioned forms. However, traditionalist scholars criticize these approaches for potentially relativizing divine guidance. The research proposes an integrative hermeneutical framework combining classical Islamic concepts like asbab al-nuzul and maqasid al-shariah with Western hermeneutical theory, particularly attention to context and dialogical understanding. This framework requires clear methodological criteria, theological safeguards, and procedural transparency. The findings demonstrate that successful integration maintains Islamic theological integrity while incorporating valuable interpretive insights addressing contemporary Muslim realities, providing methodological guidance for scholars and religious educators.